2021
DOI: 10.1371/journal.pgen.1009462
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of Down syndrome: Maternal MCM9 polymorphisms increase risk of reduced recombination and nondisjunction of chromosome 21 during meiosis I within oocyte

Abstract: Altered patterns of recombination on 21q have long been associated withthe nondisjunction chromosome21within oocytes and the increased risk of having a child with Down syndrome. Unfortunately the genetic etiology of these altered patterns of recombination have yet to be elucidated. We for the first time genotyped the gene MCM9, a candidate gene for recombination regulation and DNA repair in mothers with or without children with Down syndrome. In our approach, we identified the location of recombination on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“… 78 Birth of child with Down syndrome Pal et al. 79 Infertility, female AlAsiri et al., Tenenbaum-Rakover et al., Dou et al., Desai et al., Bouali et al., Zhang et al., Heddar et al., Wang et al., Jin et al., Tucker et al. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 Desai et al., Alvarez-Mora et al., Fauchereau et al., França et al., Goldberg et al., Guo et al., Liu et al., Shen et al., Turkyilmaz et al., Wood-Trageser et al., Yang et al., and Jolly et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 78 Birth of child with Down syndrome Pal et al. 79 Infertility, female AlAsiri et al., Tenenbaum-Rakover et al., Dou et al., Desai et al., Bouali et al., Zhang et al., Heddar et al., Wang et al., Jin et al., Tucker et al. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 Desai et al., Alvarez-Mora et al., Fauchereau et al., França et al., Goldberg et al., Guo et al., Liu et al., Shen et al., Turkyilmaz et al., Wood-Trageser et al., Yang et al., and Jolly et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Pal et al. 79 identified a multitude of MCM9 polymorphisms in the genomes of women with a Down syndrome child (OMIM 190685 ), hypothesizing that the variants may increase the chance of a child with Down syndrome because of their association with the recombination and nondisjunction of chromosome 21 at meiosis I stage of oogenesis in a maternal age-independent manner. Moreover, Bally et al.…”
Section: Resultsmentioning
confidence: 99%
“…They are also more likely to be sleep-deprived, have an imbalanced diet to control body weight. Recent studies have identified some genetic predispositions (just as consanguineous marriage, maternal telomere length, maternal MCM9 polymorphisms, maternal Presenilin-1 and Apolipoprotein E polymorphisms) of women that may cause nondisjunction and Down syndrome birth at younger age ( Ray et al, 2016 ; Bhaumik et al, 2017 ; Ray et al, 2018 ; Pal et al, 2021 ). These are age-independent risk factors.…”
Section: Discussionmentioning
confidence: 99%